WINE AGING AND THE SCIENCE OF BARRELS: A STUDY ON THE USE OF OREGON OAK AS AN ALTERNATIVE TO IMPORTED OAK IN AGING PORTLAND WINES AND ITS IMPACT ON FLAVOR DEVELOPMENT - Корчевська, Юлія (SWorldJournal, 2025)
The article examines the use of Oregon oak as an alternative to imported oak in aging Portland wines and its impact on flavor development. The study aims to establish the relationship between the properties of Oregon oak wood and the quality and organolep